Implementasi Program Penyuluhan Anti-Bullying oleh Mahasiswa KKN UNP kepada Anak-Anak Nagari Harau - Armaita Armaita; Fathimah El Hafidzoh; Najwa Cahaya Addyp; Sabila Fijra Hidayatika; Sela Febriana; Nilam Alya Putri (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2025)
Bullying remains a serious issue in elementary school environments that has negative impacts on children’s mental health, social relationships, as well as emotional and character development. Recognizing the importance of early prevention efforts, students of the Community Service Program (Kuliah Kerja Nyata/KKN) from Universitas Negeri Padang (UNP) initiated and implemented an anti-bullying outreach program for children in Nagari Harau. This program aims to increase children’s awareness, understanding, and sensitivity toward various forms of bullying, including physical, verbal, and non-verbal bullying, as well as to introduce the impacts caused and simple strategies to deal with and prevent such behavior. The outreach activities were carried out using participatory and interactive methods to ensure the material was easily understood by children, supported by PowerPoint presentations, educational quizzes, light discussions, and simulations of everyday situations relevant to their lives. The target participants were elementary school students in the Nagari Harau area who are vulnerable to bullying practices in school and social settings. The evaluation results showed a significant improvement in participants’ understanding of bullying, where only about 30% of participants understood the material before the activity, increasing to 85% after the program was implemented. Positive responses from children, teachers, and the local community emphasize the importance of this program as an effective form of social intervention. This program demonstrates that child-friendly educational approaches can contribute to creating a safer, more comfortable, and bullying-free learning environment.